TINJAUAN HUKUM KEDUDUKAN DAN FUNGSI GUBERNUR MENURUT UU NO. 9 TAHUN 2015 TENTANG PERUBAHAN UU NO. 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Yusuf Djabbar (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2018)
This study aimed to how the position and function of the Governor in the implementation of regional autonomy granted by Law No. 23 year off in 2014 and how the position and function of the ideal governor in the implementation of regional autonomy.The results showed that the position and function of the Governor contained in the legislation gives the governor position as an arm of the central government and coordinate the governance between the Central Government and the Regions., And has not been implemented to the maximum Due to remember the law is simpulation has not lasted 2 years and there are inadequacies in chapters chapter weaknesses which, if interpreted led to overlapping of authority. Which ideally is supposed Governor as the head of the local government as well as the head of the autonomous region. Regent / mayor is responsible to the Governor while Governor responsible to Parliament and can be imposed by Parliament.Law No. 23 of 2014 concerning regional governments need to be reviewed with due regard to powers that should be implemented by The government's in the area as well as firmness and clarity in rationing and the implementation of the maximum.